THE MARKETING STRATEGY IN PD. JABAR HADI BENGKULU - Cornelia Nubatonis; Neri Susanti; Mimi Kurnia Nengsih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
Marketing is a social and managerial process by which individuals and groups obtain their needs and wants by creating, offering, and exchanging things of value with one another. Marketing strategy is an activity of selecting and explaining one or more target markets and developing and maintaining a marketing mix that will produce consumers with the target market. The purpose of marketing is to find out how the marketing strategy in PD. West Java Hadi Bengkulu. This type of research is descriptive research with qualitative methods, namely identifying internal strengths, weaknesses and identifying external opportunities and threats faced by PD. Jabar Hadi in marketing products, in order to obtain the most appropriate strategy that can be used in the future. The data collection method used a questionnaire with a sample of 25 respondents with incidental sampling technique with SWOT analysis method. From the results of the research on the calculation of IFAS and EFAS in this study, there are strengths that PD has. West Java Hadi Bengkulu is 1.41 while the weakness is 1.54, so the cell (quadrant) internal factor is 1.41 1.54 = 0.13, while the opportunity is 1.72 with a threat of 1.4, so the cell ( quadrant) external factor is 1.72 1.4 = 0.32 so it is in cell (quadrant) 1 in the SWOT analysis diagram.